RELASI KEKUASAAN, KEPENTINGAN DAN LEGITIMASI DALAM ANALISA POLITIK - AHMAD TAUFAN DAMANIK (Politeia: Jurnal Ilmu Politik, 2012)
The post-reformation, Indonesia politics is marked by an extraordinary leap. This study explain relation of power, interests and legitimation in political analysis especially base on political system and discourse analysis approach. Collecting data using library research and documents. This study found that there are important notes from the analysis on political system after the amendment of Constitution 1945. Firstly, there is split of power into new political institutions. Secondly, fragmentation is also followed by the dysfunctional of government institutions. Third-ly, there are inconsistencies in the constitutional structure and laws. Forth, the position of ad-hoc institutions becomes more important than permanent ones. Fifth, decentralization does not generate distribution of economic political power as part of the idea of pluralism and political recognition. Sixth, the multi-parties system never succeeds creating the power of political. Sev-enth, it is the weakening civil society power and organizational interest as well as the fading of uniting factors and elements.Keywords: Power, interests, legitiomation, political system.